2019
DOI: 10.1016/j.pscychresns.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

EEG recording during an emotional face-matching task in children of mothers with interpersonal violence-related posttraumatic stress disorder

Abstract: EEG recording during an emotional face-matching task in children of mothers with interpersonal violencerelated posttraumatic stress disorder,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…With respect to previous results obtained by the Geneva Early Childhood Stress Project (GECS-Pro; Moser et al, 2015 ; Perizzolo et al, 2019 ) that demonstrated effects of maternal IPV-PTSD on mothers identification and comprehension, as well as child appraisal of emotions using brain imaging, our specific hypotheses were the following:…”
Section: Introductionmentioning
confidence: 93%
“…With respect to previous results obtained by the Geneva Early Childhood Stress Project (GECS-Pro; Moser et al, 2015 ; Perizzolo et al, 2019 ) that demonstrated effects of maternal IPV-PTSD on mothers identification and comprehension, as well as child appraisal of emotions using brain imaging, our specific hypotheses were the following:…”
Section: Introductionmentioning
confidence: 93%
“…However, studies using different designs and methodologies were included and current evidence remains limited. Moreover, it is also important to consider maternal traumatic events experienced since the time of the child's birth, as this is a sensitive period to create a healthy mother-child relationship (31). Accordingly, the objectives of this study were to: 1) examine longitudinally the effect of maternal IPV-PTSD when children were ages 1-3.5 years old on specific child psychopathology (i.e., anxiety, behavioral problems, and major depressive symptoms) when children were 5-9 years old; 2) investigate the associations of maternal lifetime experience of IPV events on child psychopathology; 3) assess the association between children's lifetime exposure to violence and the development of child psychopathology.…”
Section: Introductionmentioning
confidence: 99%